Pengembangan Bahan Ajar Matematika Berbasis Realistic Mathematics Education Untuk Melatih Keterampilan Berpikir Kreatif Kelas IV SD Negeri Kota Bengkulu - Prima Alfurqon; Victoria Karjiyati; Pebrian Tarmizi (JURIDIKDAS, 2022)
This study develops teaching materials mathematical approach Realistic Mathematics Education (RME) to train the creative thinking skills of fourth grade Elementary School Bengkulu City as a reference material for students. This study is a Research and Development (R&D) research modifying the ADDIE model. This research was conducted in five stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. Validation is carried out by material experts, design experts, and linguists. Teaching materials that have been validated are given to fourth grade teachers of Bengkulu City Elementary Schools to get responses. Data analysis techniques in this study are qualitative descriptive statistical analysis of input, comments, and suggestions from expert validation sheets, teacher response questionnaires, student summative evaluation results, student response questionnaires and descriptive statistical analysis of scores from expert validation results, teacher responses and responses. students. This research produces teaching material products with expert validation assessment of material 94.2, expert validation design 92.5, validation of linguists 85.71 with very valid categories. The results of eligibility get 92.22 with a very valid category and the effectiveness of getting 87,75 with a very effective category. The conclusion of this research is that the product of developing mathematics teaching materials based on Realistic Mathematics Education is valid, feasible, and effective to be used to train the creative thinking skills of class IV Elementary Schools of Bengkulu City.Keywords: Teaching Materials, Development, RME, Creative Thinking Skills,                     Mathematics.